Case Report: De novo Variants of KMT2E Cause O'Donnell-Luria-Rodan Syndrome: Additional Cases and Literature Review - Li, Yang; Fan, Lijuan; Luo, Rong; Yang, Zuozhen; Yuan, Meng; Zhang, Jinxiu; Gan, Jing (Frontiers in Pediatrics, 2021)
Introduction: O’Donnell-Luria-Rodan syndrome was recently identified as an autosomal dominant systemic disorder caused by variants in KMT2E. It is characterized by global developmental delay, some patients also exhibit autism, seizures, hypotonia, and/or feeding difficulties. Methods: Whole-exome sequencing of family trios were performed for two independent children with unexplained recurrent seizures and developmental delay. Both cases were identified as having de novo variants in KMT2E. We also collected and summarized the clinical data and diagnosed them with O’Donnell-Luria-Rodan syndrome. Structural-prediction programs were used to draw the variants’ locations. Results: A 186 G>A synonymous variant (NM_182931.3:exon4: c.186G>A (p.Ala62=)) was found in one family, resulting in alternative splicing acid. A 5417 C>T transition variant (NM_182931.3:exon27: c.5417C>T (p.Pro1806Leu)) was found in another family, resulting in 1806 Pro-to-Leu substitution. Both variants were classified as likely pathogenic according to the ACMG (American College of Medical Genetics and Genomics) guideline, and verified by Sanger sequencing. Conclusion: To date, three studies of O’Donnell-Luria-Rodan syndrome have been reported with heterogeneous clinical manifestations. As a newly recognized inherited systemic disorder, O’Donnell-Luria-Rodan syndrome needs to be paid more attention, especially in gene testing.